Devil's staircases without particle-hole symmetry - Lan, Zhihao; Lesanovsky, Igor; Li, Weibin (American Physical Society, 2018)
We present and analyze spin models with long-range interactions whose ground state features a so-called devil’s staircase and where plateaus of the staircase are accessed by varying two-body interactions. This is in contrast to the canonical devil’s staircase, for example occurring in the one-dimensional Ising model with long-range interactions, where typically a single-body chemical potential is varied to scan through the plateaus. These systems, moreover, typically feature a particle-hole symmetry which trivially connects the hole part of the staircase (filling fraction f ≥ 1/2) to its particle part (f ≤ 1/2). Such symmetry is absent in our models and hence the particle sector and the hole sector can be separately controlled, resulting in exotic hybrid staircases.